2016
DOI: 10.1111/modl.12317
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Synchronous and Asynchronous Written Corrective Feedback on Grammatical Accuracy in a Computer‐Mediated Environment

Abstract: This study extends research on written corrective feedback (CF) by investigating how timing of CF affects grammar acquisition. Specifically, it examined the relative effects of synchronous and asynchronous CF on the accurate use of the hypothetical conditional structure. Participants were 68 intermediate‐level students of English at a university in Japan. Learners from a synchronous CF group (SCF), an asynchronous CF group (ACF), and a comparison group completed 2 writing tasks using Google Docs. The 2 experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 39 publications
5
86
0
4
Order By: Relevance
“…One recent study by ref [2] found that using synchronous corrective feedback improved students' accuracy in posttests as compared with a comparison group that only received ACF. They observed that new software such as google docs ™ and Microsoft's Skydrive ™ allow what is a relatively new opportunity for SCF both practically in classroom pedagogy and in terms of SLA.…”
Section: B Synchronous Vs Asynchronous Feedbackmentioning
confidence: 96%
See 4 more Smart Citations
“…One recent study by ref [2] found that using synchronous corrective feedback improved students' accuracy in posttests as compared with a comparison group that only received ACF. They observed that new software such as google docs ™ and Microsoft's Skydrive ™ allow what is a relatively new opportunity for SCF both practically in classroom pedagogy and in terms of SLA.…”
Section: B Synchronous Vs Asynchronous Feedbackmentioning
confidence: 96%
“…Reference [2] describes programmes like Google Docs ™ as -online simultaneous editing software‖. This kind of programme is a relatively recent tool to language teachers and offers new opportunities in a computer mediated learning environment for real time focus on form via synchronous corrective feedback (SCF) and negotiation of meaning, a key aspect of collaborative writing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations